Comparison of web application state management tools - Szymanek, Kacper; Pańczyk, Beata (Journal of Computer Sciences Institute, 2021)
Modern web applications require flow of large amounts of data. To maintain order in code, a state manager was invented. With manager all data can be retrieved from and goes to one place. In this paper, four libraries for state management (NgRx, Ngxs, Redux, Vuex) were analyzed. Five criteria were used for the study: code metrics, solution structure, availability of ready-made implementations, community support, and performance testing. Results showed that there is not the best tool in every criterion, but when comparing the results obtained, the most universal solution is Vuex.